Role of polaron dressing in superradiant emission dynamics - J. Wiercinski; M. Cygorek; E. M. Gauger (Physical Review Research, 2024)
Cooperative effects of multiple quantum emitters are characterized by transitions via delocalized collective states with altered emission properties due to the existence of interemitter coherences. When realized with excitonic condensed-matter nanostructures, these effects are significantly affected by the presence of strong emitter-phonon coupling, which leads to the formation of polarons. We show that, while for single-emitter emission into free space this formation has no impact on its radiative lifetime, the same is not true for superradiant emission. Considering the case of two indistinguishable quantum emitters, we analyze how polaron dressing affects collective photon emission by mixing bright and dark Dicke states. Our numerical simulations show that this mixing crucially depends on the circumstances of the excitation of the system: Depending on the pulse length of an exciting laser, one can choose to either prepare polaronic Dicke states, or bare electronic Dicke states, changing the superradiant decay characteristics of the system. Additionally, we derive analytic expressions for these limiting cases, which match the results of numerically exact calculations.